CSR Campaign: Raising Public Awareness of Health at the World Diabetes Day Event - Syahril Ramadhan, Raden Muhammad; Alfitri, Alfi Alifa; Khumayah, Siti; Lestari, Aghnia Dian (Greenation Publisher & Yayasan Global Resarch National, 2025)
One of the ways the companies use to make a decent society is through their Corporate Social Responsibility (CSR) campaigns. This research analyzes the CSR program of PT Nutrifood, in the World Diabetes Day 2024 in disseminating the importance of diabetes. As part of a qualitative approach combined with descriptive analysis, this paper discusses the effect of the campaign on the public knowledge and practice towards health as a way of life. One of the projects to this campaign is the campaign to educate people, through “1 Month of Reducing Sugar Consumption” activities, aiming to raise awareness of society about the mindful control of sugar consumption, every day. The findings of this study indicated that the CSR activity in the form of the campaign “I Give My #Hands4Diabetes In World Diabetes Day 2024” could improve public concern about the balance diet, sugar consumption, and the support to involve in health activities. It also helped build up company's brand and customer loyalty. By practicing the Triple Bottom Line (Profit, People, and Planet), PT Nutrifood doesn’t only concentrate on financing, but also contributes to improving social welfare and preserving the environment.